War and state terrorism : the United States, Japan, and the Asia-Pacific in the long twentieth century - Selden, Mark; So, Alvin Y., 1953- (War and peace library., 2004)
Tracing the course of conflicts throughout Asia in the past century, this groundbreaking volume is the first to explore systematically the nexus of war and state terrorism. Challenging states' definitions of terrorism, which routinely exclude their own behavior, the book focuses especially on the nature of Japanese and American wars and crimes of war. This rare comparative perspective examines the ways in which state terror leads to civilian casualties, war crimes, and crimes against humanity. In counterbalance, they discuss anti-war movements and international efforts to protect human rights.